My manners matter : a first look at being polite - Thomas, Pat.; Harker, Lesley (Hauppauge, N.Y. : Barron's, 2006)
This book helps children understand that good manners show both kindness and respect to people they know and to people they don't know.
Includes bibliography.
K-3
Keywords: Etiquette for children and teenagers